Os espaços públicos de lazer da cidade de Teresina (PI) - Santos, Laudenides Pontes dos [UNESP] (2015)
This research on the urban geography of Teresina, focuses on public recreational areas of the city, its distribution, appropriation, conservation. As a main goal, we sought to understand how the public leisure spaces in Teresina-PI are specialized, their main problems and potentialities. Leisure becomes increasingly important to life quality, since it currently has a strict separation between work time and leisure time, this is highlighted in the cities, because this separation is even more rigid. The public spaces of cities, therefore, should in a democratic manner, allow access to recreation for all people regardless of their social class, this because leisure has become an important content of urban life. The theoretical and methodological strand focused on dialectics allowed an analysis of public recreational areas of Teresina as a social phenomenon, rich in contradictions. The methodological procedures adopted were: literature review, documentary research, observation, field research with questionnaires and interviews. The spatial area of research was the city of Teresina, and the sample used were 10 districts two in each area of the city, the largest leisure public spaces existing in the city were further analyzed. The analysis undertaken in this study allowed us to observe that the city of Teresina is still very needy regarding the existence, distribution and structuring of its public spaces for leisure. It was verified that although the society has diversified its forms of leisure over time, urban policies towards equipping the neighborhoods with public spaces have not been effective. In addition, there are other barriers such as lack of maintenance of existing public spaces and urban violence that puts people off of these places